Cholesterol Esterification Enzyme Inhibition Enhances Antitumor Effects of Human Chimeric Antigen Receptors Modified T Cells. Issue 2 (February 2018) - Zhao, Lei; Li, Jun; Liu, Yang; Kang, Liqing; Chen, Huinan; Jin, Ye; Zhao, Fuya; Feng, Jing; Fang, Chengyuan; Zhu, Biqiang; Ding, Shuo; Yu, Lei; et al.
Abstract : Chimeric antigen receptor-modified T cell (CART) therapy has been demonstrated to have significant effect on hematologic tumor in patients. However, many persistent obstacles and challenges still limit the application. It is known that CD8 + T cells are a key component of antitumor immunity. An avasimibe-induced inhibition of cholesterol esterification has been shown to improve the antitumor response of CD8 + T cells in mice. In this study, using human CD19-directed CART cells as effector cells and CD19-overexpressing K562 cells as target cells, we detected whether cholesterol acyltransferase inhibition by avasimibe can enhance the antitumor effect of human CART cells. After avasimibe treatment, the infection rate was dropped by up to 50% ( P <0.05). The cytotoxic effect of CART cells was significantly increased than the control group in a dose-dependent manner. Moreover, the level of secreted interferon-γ increased in almost half of the cases ( P <0.05); the ratio of CD8 + CD4 − T cells was increased among the total T cells and the CART cells in some of cases ( P <0.05). Our study suggests that inhibition of cholesterol acyltransferase can promote the antitumor effect of CART cells, and provides a new option for a combination therapy by regulating T-cell metabolism to enhance antitumor effects. Abstract : Supplemental Digital Content is available in the text.